Potential Antitumor Activity of Combined Lycopene and Sorafenib against Solid Ehrlich Carcinoma via Targeting Autophagy and Apoptosis and Suppressing Proliferation - Thanaa A. El-Masry; Maysa M. F. El-Nagar; Nageh A. El Mahdy; Fatemah A. Alherz; Reham Taher; Enass Y. Osman (MDPI AG, 2024)
An FDA-approved kinase inhibitor called sorafenib (SOR) is used to treat primary kidney and liver cancer as well as to stop the spread of advanced breast cancer. Side effects from SOR, such as palmar-plantar erythrodysesthesia syndrome, can negatively impact an individual's quality of life. There are a lot of data supporting the importance of lycopene (LYC) in preventing cancer. The antitumor properties of the combination of sorafenib and lycopene were examined in this study. A viability test against MDA-MB-231 was used to assess the anticancer efficacy of sorafenib, lycopene, and their combination in vitro. Moreover, a cell cycle analysis and Annexin-V/PI double staining were performed by using flow cytometry. In addition, the protein level of JNK-1, ERK-1, Beclin-1, P38, and P53 of the MDA-MB-231 cell line was estimated using ELISA kits. In addition, mice with SEC were divided into four equal groups at random (n = 10) to investigate the possible processes underlying the in vivo antitumor effect. Group IV (SEC-SOR-LYC) received SOR (30 mg/kg/day, p.o.) and LYC (20 mg/kg/day, p.o.); Group I received the SEC control; Group II received SEC-SOR (30 mg/kg/day, p.o.); and Group III received SEC-LYC (20 mg/kg/day, p.o.). The findings demonstrated that the combination of sorafenib and lycopene was superior to sorafenib and lycopene alone in causing early cell cycle arrest, suppressing the viability of cancer cells, and increasing cell apoptosis and autophagy. Likewise, the combination of sorafenib and lycopene demonstrated inhibition of the levels of Bcl-2, Ki-67, VEGF, IL-1β, and TNF-α protein. Otherwise, the quantities of the proteins BAX, P53, and caspase 3 were amplified. Furthermore, the combined treatment led to a substantial increase in TNF-α, caspase 3, and VEGF gene expression compared to the equivalent dosages of monotherapy. The combination of sorafenib and lycopene enhanced apoptosis and reduced inflammation, as seen by the tumor's decreased weight and volume, hence demonstrating its potential anticancer effect.